Bersinergi Membangun Desa Menuju Enterpreneur dalam Mendukung Pembangunan Desa Sukadami Berkelanjutan - Sri Wahyuningsih; Catur Sasi Kirono; Sindik Widati (CV. ITTC INDONESIA, 2026)
This paper examines the role of stakeholder collaboration in fostering village entrepreneurship as a strategy to promote sustainable development in Sukadami Village. The program focuses on joint actions involving the village administration, local residents, youth groups, and higher education institutions to optimize local economic resources. By applying participatory methods, entrepreneurial training, and continuous assistance for micro, small, and medium enterprises (MSMEs), the initiative aims to strengthen entrepreneurial capacity, creativity, and economic self-reliance within the community. The findings show that entrepreneurship-oriented village development has a positive impact on improving household income, reinforcing local organizations, and supporting long-term economic sustainability. Furthermore, effective coordination among stakeholders is essential to maintain program consistency and outcomes. The study concludes that collaborative and inclusive village entrepreneurship initiatives can serve as a viable framework for achieving sustainable rural development and enhancing community welfare.